Регіональна транспортна система та її місце в соціально-економічному розвитку регіону - Мітеллаєва, К.О. (Культура народов Причерноморья, 2013)
В статті визначено місце регіональної транспортної системи в економічному та
соціальному розвитку регіону. Проведено аналіз впливу окремих елементів регіональної транспортної
системи на економіку регіону. Визначено вплив якості дорожньо-транспортних умов на зростання
валового національного продукту та скорочення витрат бюджету В статье определено место региональной транспортной системы в экономическом и
социальном развитии региона. Проведен анализ влияния отдельных элементов региональной
транспортной системы на экономику региона. Определено влияние качества дорожно-транспортных
условий на увеличение валового национального продукта и сокращение затрат бюджета. The transport arrangement of the region in the contemporary management conditions has become
one of the most priority spheres for manifestation of common interests and for apposition of efforts both for
economic entities and executive authorities at all the levels. Therefore, the comprehensive studies of the state,
lines of development and effectiveness increase of the regional transport system, as a factor of the socioeconomic
development of the region takes on special significance.
Transport includes all the processes, by which society takes possession of the ambient space. The heterogeneity
of habitat, the variety of its parts causes the genetic increasing of the role of transportation in society. Transport
provides an uninterrupted familiarization of the space and in this sense it is the beginning, that forms a system of
this familiarization, that interacts with natural and artificial systems. A great amount of scientists dedicated
their works to the influence of transport on individual areas of social development and cost effectiveness. But
there are still the questions of the influence of transport system on socio-economic development of individual
regions, taking into account the particular features and the level of its development, that have to be examined in
future.
The aim of this article is to determine the role of the transport system in socio-economic development of the
region, the ground of factors, that have an influence on individual elements of transport system on the region’s
economy and the detection of the correlation of influence on economic and social factors.
In the article the place of regional transport system in the economic and social development of the region is
determined. The analysis of the impact of individual elements of regional transport system on the region’s
economy is carried out. The influence of the quality of traffic conditions on the growth of gross domestic product
and cut down of expenses of the budget is determined.